Analysis of Factors Influencing Brand Loyalty to International Clothing Brands in Batam City Mediated by Brand Trust - Winardy, Jeffri; Marheni, Dewi Khornida (Universitas Proklamasi 45, 2024)
This research was conducted to determine the factors influencing Brand Loyalty to international clothing brands in Batam City, which is mediated by Brand Trust. By using purposive sampling, samples obtained as many as 355 respondents. Empirical data was obtained using the online questionnaire distribution method with the Google form. The research data was tested using the Structural Equation Modeling (SEM) technique with Smart PLS 3 for Windows. The variables contained in the research are Brand Reputation, Brand Personality, Brand Experience, Brand Image, Brand Trust, and Brand Loyalty. The study results show that the variables of Brand Experience and Brand Trust affect Brand Loyalty. Variables of Brand Experience, Brand Image, Brand Personality, and Brand Reputation influence Brand Trust. Meanwhile, Brand Image, Brand Personality, and Brand Reputation variables do not affect Brand Loyalty. Brand Image and Brand Reputation variables affect Brand Loyalty when mediated by Brand Trust. Meanwhile, Brand Experience and Brand Personality do not affect Brand Loyalty when mediated by Brand Trust. This study is expected to become a reference and literature for building marketing strategies to be more effective and efficient. So it can be used by companies as a source of information and insight in making business decisions.